Sustainable Fluorescence-off Based Analytical Approach for the Quantification of Linagliptin Using a Biocompatible Sensor; Erythrosine B Dye - Hamad, Ahmed Abdulhafez; Mohammed, Bassam Shaaban; Abdelsalam Ouf, Abdelsalam Mohamed; Darwish, Ibrahim A.; Ashkar, Abdulsalam; Haredy, Ahmed M. (Journal of fluorescence, 2025)
A fluorescence quenching strategy was conceptualized to establish an environmentally compatible analytical system for trace-level detection of Linagliptin (LGP), an anti-diabetic pharmaceutical compound. This research delineates a biochemical sensing mechanism relying on an electrostatic coupling between LGP and Erythrosine B (EB), a biologically certified fluorophore, within optimized acidic parameters. The molecular association induced a concentration-dependent reduction in EB's intrinsic emission intensity at λ 554 nm, attributed to the generation of a non-luminescent LGP-EB supramolecular assembly. Methodical optimization of operational parameters governing the recognition process-including pH modulation, stoichiometric ratios, and temporal stability-yielded a linear response across 0.30-2.50 µg/mL, with detection and quantification capacities reaching 0.0286 µg/mL and 0.0943 µg/mL, respectively. Validation studies confirmed adherence to International Council for Harmonization (ICH) criteria, exhibiting ≤ 1.9% relative standard deviation in precision assessments and 98.9-100.8% recovery rates in spiked samples. The technique's efficacy was verified across multiple matrices, encompassing raw drug substances, pharmaceutical formulations, and simulated biological media. Ecological compatibility was rigorously evaluated through modern sustainability metrics aligned with green analytical chemistry principles. Implementation of the White Analytical Chemistry (WAC) protocol via the RGB 12 algorithm designated the methodology as "environmentally considerate," reflecting minimal reagent consumption and energy requirements. Concurrent analysis using the BAGI (Biocompatible Analytical Greenness Index) tool produced exceptional scores in ecological safety and methodological adaptability, confirming its proficiency in harmonizing analytical precision with sustainable practices. This dual-focused approach addresses critical needs in pharmaceutical quality control while advancing eco-responsible analytical methodologies.